Remnants of paleoflora in impact melt rocks of the El'gygytgyn crater (Chukotka, Russia) - E. P. Gurov (Institute of Geological Sciences, National Academy of Sciences of Ukraine); V. V. Permiakov (Institute of Geological Sciences, National Academy of Sciences of Ukraine); C. Koeberl (Department of Lithospheric Research, Faculty of Earth Sciences, Geography and Astronomy, University of Vienna) (Meteoritics & Planetary Science, 2019)
The abstract is available here: https://uscholar.univie.ac.at/o:996086 The abstract is available here: https://uscholar.univie.ac.at/o:996086